1997
DOI: 10.1104/pp.115.3.1241
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Blue Light Signal Transduction Chains That Control Development and Maintenance of Sexual Competence in Chlamydomonas reinhardtii

Abstract: Blue light induces the differentiation of Chlamydomonas reinhardtii pregametes to gametes. The light-induced conversion of pregametes to gametes is protein synthesis dependent and proceeds only after a lag phase. Upon incubation in the dark, gametes lost their mating ability, resulting in dark-inactivated gametes. Reillumination rapidly restored mating competence and this was shown to be independent of protein synthesis. Apparently, differentiation and maintenance of gametic competence are both regulated by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…Studies at the biochemical level have identified a protein kinase C-like activity and a tyrosine kinase (20,46). Does light signaling during gametogenesis and zygote germination use the same or different pathways?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies at the biochemical level have identified a protein kinase C-like activity and a tyrosine kinase (20,46). Does light signaling during gametogenesis and zygote germination use the same or different pathways?…”
Section: Discussionmentioning
confidence: 99%
“…Reillumination of these dark-inactivated gametes rapidly restores their mating competence. For this step, 450-nmwavelength light was shown to be most effective (20). To test a possible function of phototropin in this process, gametes of the RNAi20 strain were generated from pregametes and then incubated in the dark for 60 min.…”
Section: Involvement Of Phototropin In Maintaining Matingmentioning
confidence: 99%
See 2 more Smart Citations
“…This signal becomes effective in the late phase of sexual differentiation Weissig and Beck, 1991;Beck and Acker, 1992). Irradiation with blue light also is required to maintain the gametes' mating competence (Pan et al, 1997).…”
mentioning
confidence: 99%